Assessing the value of e-learning systems - Levy, Yair 1970- (Hershey, Pa London Information Science, 2006)
"The book provides A guidelines approach on how to implement the proposed theory and tools in e-learning programs"--Provided by publisher
Includes bibliographical references (p. 232-239) and index
3
Keywords: Computer-assisted instruction; Distance education; Education -- Computer network resources; Internet in education